Long-Term Safety and Efficacy of Nonacog Beta Pegol (N9-GP) Administered for at Least 5 Years in Previously Treated Children with Hemophilia B - Carcao, Manuel; Kearney, Susan; Lu, Meng Yao; Taki, Masashi; Rubens, Daniel; Shen, Chunduo; Santagostino, Elena (Thrombosis and Haemostasis, 2020)
Long-term safety and efficacy data of extended half-life factor IX (FIX) prophylaxis in children with hemophilia B (HB) are sparse. paradigm 5 is a multinational, open-label, single-arm, phase III trial assessing once-weekly (40 IU/kg) prophylactic nonacog beta pegol (N9-GP) in previously treated patients (PTPs) aged ≤ 12 years with HB (FIX activity ≤ 2%). Primary endpoint: incidence of anti-FIX inhibitory antibodies (≥ 0.6 Bethesda Units). We present a 5-year analysis (N = 25, including remaining patients with ≥ 5 years' follow-up) and compare with a 1-year analysis (≥ 52 weeks' exposure). The main phase enrolled 25 children; 22 entered the extension phase; 17 remained in trial at data cutoff. Median treatment period: 5.6 years/patient; median total number of N9-GP exposure days: 290.0/patient. No patients developed anti-FIX inhibitory antibodies. No other safety concerns, including thromboembolic events, were reported. Neurological examinations have not revealed any new abnormal findings. Sixteen (64.0%) patients remained free from spontaneous bleeds; all bleeds were mild/moderate in severity; 93.0% were controlled with 1 to 2 N9-GP injections. No intracranial hemorrhages were reported. Annualized bleeding rates (ABRs) were very low at 5 years (median/Poisson-estimated mean overall ABR: 0.66/0.99), having decreased from the 1-year analysis (1.00/1.44). Median/Poisson-estimated mean spontaneous ABRs for the 1- and 5-year analyses: 0.00/0.45 and 0.00/0.33. Mean FIX trough activity at 5 years: 17.9%. Mean polyethylene glycol plasma concentration reached steady state at 6 months, increasing slightly over time, in line with increased FIX trough activity. N9-GP administered for ≥ 5 years shows favorable long-term safety and efficacy in PTPs with HB (FIX activity ≤ 2%).
Keywords: N9-GP; hemophilia B; extended half-life; long-term safety; pediatric clinical trial